Adsorption Properties and Structure of Some Active Carbons - I.A. Bardina; E.V. Kalashnikova; N.V. Kovaleva; T.A. Rudnitskaya; N.K. Shonya (Adsorption Science & Technology)
Gas chromatography has been used to determine the initial low-coverage heats of adsorption of C2–C6 hydrocarbons and their derivatives on active carbon and graphitized carbon black. The porous structure of the active carbon has been determined from the adsorption isotherms of benzene measured at 25°C by a vacuum static method. The isotherms have been analyzed with the help of the BET and Dubinin–Radushkevich theories.